2021
DOI: 10.1016/j.gendis.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Sulfuretin exerts diversified functions in the processing of amyloid precursor protein

Abstract: Sulfuretin is a flavonoid that protects cell from damage induced by reactive oxygen species and inflammation. In this study, we investigated the role of sulfuretin in the processing of amyloid precursor protein (APP), in association with the two catalytic enzymes the α-secretase a disintegrin and metalloproteinase (ADAM10), and the beta-site APP cleaving enzyme 1 (BACE1) that play important roles in the generation of β amyloid protein (Aβ) in Alzheimer's disease (AD). We found that sulfuretin increased the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…The majority of immature APP is transported via vesicles to the Golgi apparatus, where it undergoes chemical modification processes, such as phosphorylation and C-terminal glycosylation, to become an active protein. Mature APP is partially processed in the Golgi by active ADAM10 enzymes [18]. However, the distribution of ADAM10 in the Golgi apparatus is relatively small relative to the cytoplasmic membrane; thus, processing is less efficient, and small amounts of BACE1 are also present in this organelle.…”
Section: App Structure and Metabolic Processesmentioning
confidence: 99%
“…The majority of immature APP is transported via vesicles to the Golgi apparatus, where it undergoes chemical modification processes, such as phosphorylation and C-terminal glycosylation, to become an active protein. Mature APP is partially processed in the Golgi by active ADAM10 enzymes [18]. However, the distribution of ADAM10 in the Golgi apparatus is relatively small relative to the cytoplasmic membrane; thus, processing is less efficient, and small amounts of BACE1 are also present in this organelle.…”
Section: App Structure and Metabolic Processesmentioning
confidence: 99%
“…Because the protein level of APP could be influenced by the proteolytic processing of BACE1 and/or ADAM10, we also assessed the effect of AP2S1 KD on APP protein expression in HEK‐APP cells treated with the BACE1 inhibitor LY2811376 35 , 36 in combination with the ADAM10 inhibitor GI254023X, 37 which are shown to alter the corresponding CTF levels. 20 As shown in Figure 2D , although LY2886721 and GI254023X together significantly increased the basal protein level of APP, they did not prevent the reduction of APP protein in HEK‐APP cells transiently transfected with AP2S1 siRNA, indicating that AP2S1‐mediated regulation of APP protein level was unrelated to the enzymatic activity of BACE1 and ADAM10. Moreover, the decreased levels of both the immature and mature forms of APP might be suggestive of an altered protein synthesis mechanism, we thus assessed the effect of AP2S1 in cells treated with protein synthesis inhibitor cycloheximide (CHX, 5 μM for 6 h).…”
Section: Resultsmentioning
confidence: 88%
“…We also found that the colocalization of APP with EEA1 was not altered by AP2S1 KD (Figure 2C), suggesting that endocytosis of APP was less likely involved in AP2S1‐mediated regulation of APP protein. Because the protein level of APP could be influenced by the proteolytic processing of BACE1 and/or ADAM10, we also assessed the effect of AP2S1 KD on APP protein expression in HEK‐APP cells treated with the BACE1 inhibitor LY2811376 35,36 in combination with the ADAM10 inhibitor GI254023X, 37 which are shown to alter the corresponding CTF levels 20 . As shown in Figure 2D, although LY2886721 and GI254023X together significantly increased the basal protein level of APP, they did not prevent the reduction of APP protein in HEK‐APP cells transiently transfected with AP2S1 siRNA, indicating that AP2S1‐mediated regulation of APP protein level was unrelated to the enzymatic activity of BACE1 and ADAM10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2 A , ADAM10 mRNA was not altered by KEN. Transcription inhibitor actinomycin D (ActD) or protein synthesis inhibitor cycloheximide (CHX) alone led to a reduced ADAM10 protein level, [ 26 ] whereas KEN‐induced ADAM10 enhancement was diminished in the presence of CHX but not ActD (Figure 2B ), suggesting an involvement of protein synthesis. It seemed that protein degradation machinery was not involved in this regulation, as the proteasomal inhibitor MG132 or the lysosomal inhibitor chloroquine (CQ) [ 16a ] failed to block KEN‐mediated augmentation of ADAM10 (Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%